Structura 2 : the art of Sparth - Sparth; Design Studio Press (Culver City, CA : Design Studio Press, 2011)
Collects images from HALO, book covers, and personal science fiction pieces with tutorials focusing on specific Photoshop techniques.
Keywords: Sparth; Graphic arts; Computer art; Fantasy in art; Science fiction in art